2009
DOI: 10.1016/j.pmrj.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Pilot Study of Painful Lumbar Facet Joint Arthropathy after Intra‐articular Injection of Hylan G‐F 20

Abstract: Viscosupplementation for lumbar FJ arthropathy with hylan G-F 20 is associated with modest efficacy that predominately lasts up to 6 months. Limitations include a small sample size and lack of both a control and blinding. Larger, randomized, controlled studies are indicated to better clarify its clinical safety, efficacy, and utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
8
0
3
Order By: Relevance
“…[75] In this study, HA scored slightly better than CS, but both reduced the VAS pain significantly. The main concern about this study was that they only report a follow-up DePalma et al, [73] of 2 months and, as shown earlier, CS act very fast and effectively, but for a shorter period.…”
Section: First Metatarsophalangeal Jointmentioning
confidence: 89%
See 1 more Smart Citation
“…[75] In this study, HA scored slightly better than CS, but both reduced the VAS pain significantly. The main concern about this study was that they only report a follow-up DePalma et al, [73] of 2 months and, as shown earlier, CS act very fast and effectively, but for a shorter period.…”
Section: First Metatarsophalangeal Jointmentioning
confidence: 89%
“…[71] The two prospective studies show an opposite outcome. Cleary et al, [72] in their prospective case series of 13 patients, showed no improvement on the VAS for pain, while DePalma et al [73] showed a significant improvement in a series of 15 patients using the same VAS for pain.…”
Section: Lumbar Facet Jointmentioning
confidence: 94%
“…However, a similar concept cannot be applied when hyaluronic acid is used, as these substances explicate their action only when injected directly in the joint space [30]. Thanks to its high tolerability and low side effects, the use of hyaluronic acid has increased in the local treatment of FJOA and could be suggested in patients with contraindication to corticosteroids [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The use of intra‐articular viscosupplements has been explored by several researchers, with a recent pilot study that demonstrated a significant improvement in low back pain, disability, function, range of motion, and sitting tolerance at 6‐month follow‐up [118]. More rigorous studies are required to investigate the role of viscosupplements in the management of facet‐mediated low back pain.…”
Section: Treatmentsmentioning
confidence: 99%